Detection of a virus-specific antigen on the surface of herpes simplex virus-transformed cells. - Reed, C L (1975)
A virion-associated antigen, CP-1, was detected on the surface of hamster cells after transformation by inactivated herpes simplex virus type 1. Presence of the CP-1 antigen on the cells correlates with the synthesis of antibody by tumorbearing hamsters capable of neutralizing both herpes simplex virus types 1 and 2.